First systematic review of the last 30 years of research on sweetpotato: elucidating the frontiers and hotspots - Meng, Xiaoqing; Dong, Tingting; Li, Zongyun; Zhu, Mingku (Frontiers in Plant Science, 2024)
Sweetpotato is an economically important crop, which has various advantages over other crops in addressing global food security and climate change. Although substantial articles have been published on the research of various aspects of sweetpotato biology, there are no specific reports to systematically crystallize the research achievements. The current review takes the lead in conducting a keyword-centric spatiotemporal dimensional bibliometric analysis of articles on sweetpotato research using CiteSpace software, in as to comprehensively clarify the development status, research hotspot and development trend in the past 30 years (1993-2022). Quantitative analysis was carried out on the publishing countries, institutions, disciplines and scholars to understand the basic status of sweetpotato research, and then visual analysis was conducted on high-frequency keywords, burst keywords, and keyword clustering, and the evolution of major research hotspots and the development trend in different periods were summarize. Finally, the three main development stages: preliminary stage (1993-2005), rapid stage (2006-2013), and diversified mature stage (2014-2022) were reviewed and analyzed in detail. Particularly, the development needs of sweetpotato production in improving breeding efficiency, enhancing stress tolerance, coordinating high yield with high quality and high resistance, and promoting demand were discussed, which will help to comprehensively understand the development dynamics of sweetpotato research from different aspects of biological exploration.